2005
DOI: 10.1038/sj.cr.7290316
|View full text |Cite
|
Sign up to set email alerts
|

Identification, characteristic and phylogenetic analysis of type II DNA topoisomerase gene in Giardia lamblia

Abstract: The genes encoding type II DNA topoisomerases were investigated in Giardia lamblia genome, and a type IIA gene, GlTop 2 was identified. It is a single copy gene with a 4476 bp long ORF without intron. The deduced amino acid sequence shows strong homology to eukaryotic DNA Top 2. However, some distortions were found, such as six insertions in the ATPase domain and the central domain, a ~100 aa longer central domain; a ~200 aa shorter C-terminal domain containing rich charged residues. These features revealed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…We first focused on understanding the role of topoisomerase II (Topo II) in Giardia . This Topo II has been reported previously [56]. Comparison of genomic and cDNA sequences showed that the topo II gene contained no introns.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We first focused on understanding the role of topoisomerase II (Topo II) in Giardia . This Topo II has been reported previously [56]. Comparison of genomic and cDNA sequences showed that the topo II gene contained no introns.…”
Section: Resultssupporting
confidence: 74%
“…A putative topoisomerase II (Topo II) has been identified in G. lamblia genome [56]. During encystation, a trophozoite may differentiate into a cyst by dividing 2 nuclei and by replicating DNA, generating a cyst with 4 nuclei [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, unclear, which type of enzyme is inhibited. A phylogenetic analysis of type II topoisomerases showed that the gene coding for the G. lamblia topoisomerase 2 (GlTop2) is eukaryote-like and thus not closely related to prokaryote topoisomerases [24]. Moreover, fluoroquinolones are effective against some apicomplexans including T. gondii most probably due to interference with the prokaryote type of translation that takes place in the apicoplast [25].…”
Section: Dna Modifying Enzymesmentioning
confidence: 99%
“…Therefore, Giardia is previously regarded as a missing link between prokaryotes and eukaryotes [25] . Although the evolutionary position of G. lamblia has been challenged by recent researches and some biologists suggest that it is possibly not the most primitive eukaryote [26][27][28][29] , G. lamblia undoubtedly represents an important primitive eukaryotic model for the study of biological evolutions. Previously, we have primarily investigated the snoRNAs in G. lamblia and found that the G. lamblia snoRNAs have unique features different from the counterparts previously identified from Archaea and other unicellular protozoan in gene structures, functions, genomic organizations and expression models [30] .…”
mentioning
confidence: 99%